Nanotechnology-based drug delivery systems for the treatment of Alzheimer's disease - Fonseca-Santos, Bruno [UNESP]; Gremião, Maria Palmira Daflon [UNESP]; Chorilli, Marlus [UNESP] (International Journal Of Nanomedicine, 2015)
Alzheimer's disease is a neurological disorder that results in cognitive and behavioral impairment. Conventional treatment strategies, such as acetylcholinesterase inhibitor drugs, often fail due to their poor solubility, lower bioavailability, and ineffective ability to cross the blood-brain barrier. Nanotechnological treatment methods, which involve the design, characterization, production, and application of nanoscale drug delivery systems, have been employed to optimize therapeutics. These nanotechnologies include polymeric nanoparticles, solid lipid nanoparticles, nanostructured lipid carriers, microemulsion, nanoemulsion, and liquid crystals. Each of these are promising tools for the delivery of therapeutic devices to the brain via various routes of administration, particularly the intranasal route. The objective of this study is to present a systematic review of nanotechnology-based drug delivery systems for the treatment of Alzheimer's disease.
Keywords: Alzheimer’s disease; Liquid crystals; Microemulsions; Nose-to-brain; Polymeric nanoparticles; Solid lipid nanocarriers; Targeted delivery